Attitudes of Students of Teacher Education Faculties in Serbia on the Concept of Quality School - Nikolić, Ivko А.; Pelemiš, Vladan M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
In order to answer the question of how to make education better in the society of the digital era, it is important to consider the attitudes and opinions of student teachers towards the characteristics of a quality school. For that purpose, the research was conducted whose goal was to determine the attitudes of students of teacher education faculties, student teachers, on the concept of a quality school as well as on the emancipatory role of students and teachers necessary for the work in a quality school. The research was conducted on a sample of 1,044 students of teacher education faculties in Serbia. The Likert scale of attitudes was applied in the research. The paper presents the results of research on the concept of a quality school that would lead every student to success. It was determined that the emancipatory role of students is best seen through the extent to which they are actively engaged in their own evaluation of their achievements; how much they prepare during their studies to accept the features of a more efficient conception of a school in which every student will succeed. The results provide a very reliable basis in modeling a quality school and effective teaching that would encourage students and lead them to success according to their individual abilities.
Keywords: student opinion; conception; schools; students' emancipatory role